D-A-D based complementary unsymmetrical squaraine dyes for co-sensitized solar cells: enhanced photocurrent generation and suppressed charge recombination processes by controlled aggregation - Singh, Ambarish Kumar; Veetil, Athulya Nellur; Nithyanandhan, Jayaraj (ACS Applied Energy Materials, 2021)
A series of donor-acceptor-donor (D-A-D) based unsymmetrical squaraine dyes have been synthesized with indoline and aniline as donor units. The sp(3)-C, N atoms of the indoline and N atom of the aniline donors are appended with alkyl groups systematically to control the self-assembly of dyes on TiO2 and to passivate the photoanode that helps in improving the open circuit voltage (V-oc) of the dye-sensitized solar cell (DSSC) device. The resulting dyes, AK1-4, possess strong absorptions between 529 and 541 nm with extinction coefficients of 1.44-1.84 X 10(5) M-1 cm(-1). Photophysical and electrochemical studies revealed that the lowest unoccupied molecular orbital and highest occupied molecular orbital of the dyes are aligned with the conduction band of TiO2 and the redox function of the electrolyte for the efficient charge injection and dye regeneration processes, respectively. A DSSC device performance for AK4 of 7.93% (V-oc of 815.88 mV and short circuit current density (J(sc)) of 12.4 mA/cm(2)) is obtained, with an incident photon to current conversion efficiency (IPCE) response of 92% at 473 nm and 86% at 566 nm without sensitizing with coadsorbent. IPCE studies revealed the equal contribution for the photocurrent generation from the H-aggregated structures. Further, such a high V-oc and DSSC efficiency have been observed first time for this class of zwitterionic dyes with the I-/I-3(-) electrolyte without sensitizing with coadsorbent. The importance of introducing the alkyl groups at the indoline as well as aniline donor units for the synergistic boosting of both V-oc, and J(sc) is compared with the model dye AK1. Complementary light absorbing dyes SQ1 and SQS4 possess absorption at 643 nm with extinction coefficients of 1.4 and 3.0 x 10(5) M-1 cm(-1), respectively. A cosensitized device performance of 9.36% is obtained for the AK4:SQS4 (1:1) combination in the I-/I-3(-) electrolyte. The IPCE profile indicates a good response over 450-700 nm with 94% at 621 nm. The importance of aggregated structures from both the dyes AK4 and SQS4 for photocurrent generation is realized.
Keywords: aggregation of dyes; co-sensitization; extension of conjugation; H-aggregate; squaraine dyes

D-A-D-based unsymmetrical thiosquaraine dye for the dye-sensitized solar cells(dagger) - Jadhav, Avinash P.; Singh, Ambarish Kumar; Maibam, Ashakiran; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Photochemistry and Photobiology, 2023)
In dye-sensitized solar cell, modulating the electronic properties of the sensitizer by varying the donor, pi-spacer, acceptor and anchoring groups help optimizing the structure of the dye for better device performance. Here, a donor-acceptor-donor-based unsymmetrical thiosquaraine sensitizer (SQ5S) has been designed and synthesized. Photophysical, electrochemical, theoretical and photovoltaic characterizations of SQ5S dye have been compared with its oxygen analog, SQ5. The incorporation of the sulfur atom in the acceptor unit of SQ5S dye showed an intense peak at 688 nm, which was 38 nm of red-shifted and showed the panchromatic light harvesting response with the onset of 850 nm compared with SQ5 dye. The LUMO and HOMO energy levels are well aligned with the conduction band of TiO2 and the redox potential of electrolyte for the charge injection and the dye-regeneration processes, respectively. Photovoltaic efficiency of 1.51% (V-OC 610 mV, J(SC) 3.07 mA cm(-2), ff 81%) has been achieved for SQ5S dye, whereas SQ5 showed the device performance of 5.43% (V-OC 723 mV, J(SC) 9.3 mA cm(-2), ff 80%). The decreased device performance for the dye SQ5S has been attributed to the favorable intersystem crossing process associated with the photoexcited SQ5S that reduces the driving force for the charge injection process.